Fresh from the laundry - Chase, Ilka; Brown, Norton (Doubleday & Company, Inc. Garden City, NY, 1967)
From Shipka to Jayce - Travel Adventures in the Balkans
Wiesbaden Prague : Vienna Budapest : Romania : Bulgaria : Yugoslavia : Greece
Keywords: Description and travel -- Communist countries; Description and travel -- Europe; Travel